Optimized protocol for high-vacuum scanning electron microscopy analysis of polyacrylamide hydrogel-attached sperm cells in a binary system - Ebel, Francisca (2024)
A protocol for the analysis of a binary system comprising polyacrylamide hydrogel-attached sperm cells using high-vacuum scanning electron microscopy (SEM) is presented. This protocol focuses on optimizing the SEM procedure to obtain accurate and detailed imaging of the sperm cells and their interactions with the hydrogel scaffold. The methodology involves a stepwise sample preparation, including sample dehydration through a gradual exchange of ethanol/water ratios, followed by the application of a conductive metal coating. By employing this modified protocol, the traditional use of acetone dehydration, which may introduce chemical alterations to the materials, is avoided. The proposed approach enables a comprehensive evaluation of the morphology and interactions within the biological system in contact with the soft material scaffold. Furthermore, the potential application of this protocol extends to the study of other mammalian reproductive cells or cells of different origins adhered to hydrogel scaffolds. Research Highlights: Novel SEM protocol reveals precise imaging of sperm-hydrogel attachment in a binary system, enhancing our understanding of cell-material interactions. By optimizing SEM procedures, the protocol achieves precise imaging of sperm-hydrogel interactions using ethanol/water dehydration and a conductive metal coating. This modified approach enables a thorough assessment of morphology and interactions in the binary system,extending its potential applicability to other reproductive cells on hydrogelscaffolds.